Pengaruh Kepemimpinan Kepala Sekolah dan Kreatifitas Guru Terhadap Hasil Belajar Siswa di MTs Nurul Furqon, Cibinong, Bogor - M Daud; Qowaid Qowaid; Mohammad Jaenudin (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2020)
The background of this research problem is the assumption that school principals and teachers as the main causes of low student learning outcomes such as the National Examination Score and Student Graduation are not in line with expectations or the ranking has dropped. The purpose of this study was to determine the joint effect of Principal Leadership and Teacher Creativity on Student Learning Outcomes at MTs Nurul Furqon, Cibinong, Bogor. The research method used in this study is a quantitative method. This research is correlational because the research seeks to investigate the effect of Principal Leadership and Teacher Creativity on Student Learning Outcomes at MTs Nurul Furqon, Cibinong, Bogor. Data collection techniques using the study of literature, documentation, observation, and questionnaires. The population and sample were students of MTs Nurul Furqon, Cibinong, Bogor. Research respondents numbered 127 class IX students. Data analysis techniques using correlation and regression analysis. The results showed that (a) the Principal's Leadership contributed very significantly and influenced very high and the direction of a positive relationship to student learning outcomes in MTs Nurul Furqon, Cibinong, Bogor Regency based on α = 0.05 r count = 0.993 and r table with N = 127 in the significance level of 5% = 0.174. Then rx1y = 0.993 means r count> r table. Comparison of r count with r table shows that r count is greater than r table that is 0.993 or 99.3% for the Principal Leadership variable (X1). (b) Teacher creativity gives a very significant contribution and very high influence and direction of a positive relationship to student learning outcomes in MTS Nurul Furqon, Cibinong, Bogor Regency based on α = 0.05 r count = 0.9877 and r table with N = 127 in the significance level of 5% = 0.174. Then rx2y = 0.9877 means r arithmetic> r table. Comparison of r arithmetic with r table shows that r arithmetic is greater than r table that is 0.9877 or 98.77% for the Teacher Creativity variable (X2). (c) The Principal's Leadership and Teacher's Creativity together contribute very significantly and have a very high influence and direction of a positive relationship to student learning outcomes at MTS Nurul Furqon, Cibinong, Bogor Regency based on α = 0.05 r count = 0.9935 and r table with N = 127 in the significance level of 5% = 0.174. Then rx2y = 0.9935 means r count> r table. Comparison of r count with r table shows that r count is greater than r table that is 0.9935 or 99.35% for the variable Principal Leadership and Teacher Creativity.